Nghiên cứu lý thuyết cơ chế phản ứng của gốc metylidin với hidro xyanua - Thọ, Nguyễn Hữu; Huệ, Nguyễn Thị Minh (Vietnam Journal of Chemistry, 2012)
The reaction mechanism of methylidene radical (CH) with hydrogen cyanide (HCN) has been studied by the Density Functional Theory (DFT) using B3LYP functional and the 6-311++G(d,p), 6-311++G(3df,2p) basis sets. The potential energy surface (PES) for the CH+HCN system has been established completely. The formation of the products H2+CCN, H2+CNC, H+HCCN(cycle) were been discussed in detail. This study would be contributing to understand more about the reaction mechanisms of the methylidyne radical with many small radicals and molecules in the atmosphere and combustion chemistry.